Effects of statins and steroids on coronary artery disease and stroke in patients with interstitial lung disease and pulmonary fibrosis: A general population study. - Jun-Jun Yeh (Public Library of Science (PLoS), 2021)
Purpose To determine the effects of statins and steroids on the risk of coronary artery disease (CAD) and stroke in patients with interstitial lung disease and pulmonary fibrosis (ILD-PF). Methods We retrospectively enrolled patients with ILD-PF who were using statins (statin cohort, N = 11,567) and not using statins (nonstatin cohort, N = 26,159). Cox proportional regression was performed to analyze the cumulative incidence of CAD and stroke. Adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) of CAD and stroke were determined after sex, age, and comorbidities, as well as the use of inhaler corticosteroids (ICSs), oral steroids (OSs), and statins, were controlled for. Results Compared with those of patients without statin use, the aHRs (95% CIs) of patients with statin use for CAD and ischemic stroke were 0.72 (0.65-0.79) and 0.52 (0.38-0.72), respectively. For patients taking single-use statins but not ICSs/OSs, the aHRs (95% CIs) for CAD and ischemic stroke were 0.72 (0.65-0.79)/0.69 (0.61-0.79) and 0.54 (0.39-0.74)/0.50 (0.32-0.79), respectively. For patients using ICSs/OSs, the aHRs (95% CIs) for CAD and ischemic stroke were 0.71 (0.42-1.18)/0.74 (0.64-0.85) and 0.23 (0.03-1.59)/0.54 (0.35-0.85), respectively. Conclusions The findings demonstrate that statin use, either alone or in combination with OS use, plays an auxiliary role in the management of CAD and ischemic stroke in patients with ILD-PF.